In situ studies into the characterisation and degradation of blue ballpoint inks by diffuse reflectance visible spectroscopy1. Issue 12 (21st June 2015) - Sauzier, Georgina; Giles, Peter; Lewis, Simon W.; van Bronswijk, Wilhelm
<x xml:space="preserve">Abstract</x> Diffuse reflectance visible spectroscopy with chemometrics was used to discriminate blue ballpoint inks in situ, with subsequent investigation of the effects of ageing.